Bioactive glass inhibits tumor development from giant cell tumor of bone-derived neoplastic stromal cells in a chicken chorioallantoic membrane assay - Fellenberg, Jörg; Losch, Sarina; Marinescu, Max R.; Frey, Birgit; Lehner, Burkhard; Arango-Ospina, Marcela; Hadzhieva, Zoya; Boccaccini, Aldo R.; Westhauser, Fabian (Cancers, 2023)
Tumor recurrence is a major problem during the treatment of giant cell tumors of bone (GCTB). We recently identified tumor cell-specific cytotoxic effects of bioactive glasses (BGs) toward neoplastic stromal cells derived from GCTB tissue (GCTSCs) in vitro. Since these data indicated a promising role of BGs in the adjuvant treatment of GCTBs, we aimed to investigate the transferability of the in vitro data into the more complex in vivo situation in the current study. We first analyzed the cytotoxicity of three different BGs in vitro by WST-1 assay after co-cultivation with primary GCTSC cell lines. The effects of BGs on tumor engraftment and growth were analyzed by chicken chorioallantoic membrane (CAM) assays and subsequent quantification of tumor take rates and tumor volumes. In vitro, all tested BGs displayed a cytotoxic effect on GCTSCs that was dependent on BG composition, concentration, and particle size. Comparable effects could be observed within the in vivo environment resulting in reduced tumor take rates and tumor volumes in BG-treated samples. These data indicate a possible clinical application of BGs in the context of GCTB therapy, mediating a reduction of recurrence rates with the simultaneous promotion of bone regeneration.
Gesehen am 20.04.2023